A review of recent literature on icing phenomena: Transport mechanisms, their modulations and controls. (October 2020) - Zhao, Y.; Guo, Q.; Lin, T.; Cheng, P.
Highlights: Fundamentals of icing nucleation dynamics and advancing of freezing phase front are reviewed. Transport phenomena in freezing of droplets, desublimation/sublimation, and condensation frosting are discussed. Mechanisms of a few recently revealed phenomena in icing are illustrated. Recent progresses in anti-/de- icing methods are summarized. Abstract: Icing is one of the most fascinating phenomena occurring ubiquitously in nature and multiple industrial applications. In spite of a century of research work on this topic, an in-depth physical description of icing process is still missing due to the unorthodox behaviors of water during solidification. In recent years, many important features pertaining to some ultrafast and microscale phenomena in icing have been revealed using latest experimental techniques and newly developed numerical simulation methods. This work aims to present a comprehensive up-to-date review on the subject of icing. Fundamentals of icing nucleation dynamics are introduced, followed by discussion on propagations of freezing phase fronts. Different forms of icing, including freezing of droplets, desublimation/sublimation, and condensation frosting, are presented sequentially. Emphasis is placed on a few recently revealed phenomena, such as dendritic ice growth through desublimation, kinetic behaviors of droplets upon freezing, frost spreading by building icing bridges, etc. A summary of recent progress in the application of anti-/de- icing methods is also presented. The results of these studies not only improve our understanding of physical mechanisms on icing, but also benefit the understanding of solidification processes in other disciplines with different applications.